Identification of two novel papillomaviruses in belugas - Li, Youyou; Xiao, Meifang; Zhang, Yun; Li, Zihan; Bai, Shijie; Su, Haoxiang; Peng, Ruoyan; Wang, Gaoyu; Hu, Xiaoyuan; Song, Xinran; Li, Xin; Tang, Chuanning; et al. (Frontiers in Microbiology, 2023)
Papillomaviruses (PVs) can cause hyperplasia in the skin and mucous membranes of humans, mammals, and non-mammalian animals, and are a significant risk factor for cervical and genital cancers. Using next-generation sequencing (NGS), we identified two novel strains of papillomavirus, PV-HMU-1 and PV-HMU-2, in swabs taken from belugas (Delphinapterus leucas) at Polar Ocean Parks in Qingdao and Dalian. We amplified the complete genomes of both strains and screened ten belugas and one false killer whale (Pseudorca crassidens) for the late gene (L1) to determine the infection rate. In Qingdao, 50% of the two sampled belugas were infected with PV-HMU-1, while the false killer whale was negative. In Dalian, 71% of the eight sampled belugas were infected with PV-HMU-2. In their L1 genes, PV-HMU-1 and PV-HMU-2 showed 64.99% and 68.12% amino acid identity, respectively, with other members of Papillomaviridae. Phylogenetic analysis of combinatorial amino acid sequences revealed that PV-HMU-1 and PV-HMU-2 clustered with other known dolphin PVs but formed distinct branches. PVs carried by belugas were proposed as novel species under Firstpapillomavirinae. The discovery of these two novel PVs enhances our understanding of the genetic diversity of papillomaviruses and their impact on the beluga population.